2024
DOI: 10.1371/journal.pgph.0002317
|View full text |Cite
|
Sign up to set email alerts
|

“Getting pregnant during COVID-19 was a big risk because getting help from the clinic was not easy”: COVID-19 experiences of women and healthcare providers in Harare, Zimbabwe

Zivai Mupambireyi,
Frances M. Cowan,
Elizabeth Chappell
et al.

Abstract: The COVID-19 pandemic and associated measures may have disrupted delivery of maternal and neonatal health services and reversed the progress made towards dual elimination of mother-to-child transmission of HIV and syphilis in Zimbabwe. This qualitative study explores the impact of the pandemic on the provision and uptake of prevention of mother-to-child transmission (PMTCT) services from the perspectives of women and maternal healthcare providers. Longitudinal in-depth interviews were conducted with 20 pregnan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Findings from eight researches showed that both quantitative and qualitative data collectively emphasize the adverse effects of COVID-19 on treatment engagement within the HIV care continuum in low-income countries, including missed refill visits, perceived impact on care and treatment, interruptions in treatment schedules, and compromised access to specialized services. [ 14 , 25 , 27 , 28 , 30 , 35 , 36 , 40 ]. Only one study among them also reported a positive effect [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Findings from eight researches showed that both quantitative and qualitative data collectively emphasize the adverse effects of COVID-19 on treatment engagement within the HIV care continuum in low-income countries, including missed refill visits, perceived impact on care and treatment, interruptions in treatment schedules, and compromised access to specialized services. [ 14 , 25 , 27 , 28 , 30 , 35 , 36 , 40 ]. Only one study among them also reported a positive effect [ 25 ].…”
Section: Resultsmentioning
confidence: 99%